(untitled) (Medicine Today, 2013)
This case report describes the treatment of an external infection related root resorption in a maxillary left central incisor which perforated the root canal apical to the cervical area. Since the resorptive perforation was large with concomitant bony lesion, treatment with a combination of nonsurgical and surgical approach was chosen. After a surgical flap was reflected, the pathologic defect was curetted, root canal space was dried and the resorptive defect was repaired with light-cured glass ionomer cement. At the same visit, root canal filled with gutta percha by lateral condensation technique and the bony cavity was filled with calcium hydroxyappatite crystal. After 18 months, the patient remained asymptomatic and the tooth was functional. DOI: http://dx.doi.org/10.3329/medtoday.v24i1.14117 Medicine TODAY Vol.24(1) 2012 pp.48-51